Periodismo biomédico, nuevos contenidos mediáticos - Moreno Espinosa, Pastora (Estudios sobre el Mensaje Periodístico, 2010)
Each of the mass media is a means of communicating with different personalities, with a different approach when dealing with a theme and identity and self-image. All this makes them different connotations for readers. These differences are apparent in the emphasis, inclusion, exclusion, preparation, cover design and writing headlines, and even to the extent that dedicated to the topic discussed. The study of the wide range of contacts and relationships between two worlds historically linked, as are the medical issues with the media in general has grown in recent decades of the last century new nuances that bring new insights on the subject and that we believe the media are a good reflection of this. In our research we aim to contribute to the study of journalism in the post health sections of newspapers.
Keywords: Health; Mass-media; Digital; Biomedical expertise